Respuesta :

Answer:

x= 6

Step-by-step explanation:

3(x + 4) = 2x + 4x - 6

3x + 12 = 2x + 4x - 6

3x + 12 = 6x - 6

-3x = -18

x= 6

hope it helps

if it helps you, pls give me the brainliest.

Wolfyy

Answer:

x = 6

Step-by-step explanation:

3(x + 4) = 2x + 4x - 6

~Distribute the left side

3x + 12 = 2x + 4x - 6

~Combine like terms on the right side

3x + 12 = 6x - 6

~Subtract 12 to both sides

3x = 6x - 18

~Subtract 6x to both sides

-3x = -18

~Divide -3 to both sides

x = 6

Best of Luck!

ACCESS MORE